A CPW-Fed Dual-Band-Notched Antenna with Sharp Skirt Selectivity for UWB Applications - Dacheng Dong; Shaojian Chen; Zhouying Liao; Gui Liu (International Journal of Antennas and Propagation)
A coplanar waveguide- (CPW-) fed dual-band-notched antenna with sharp skirt selectivity for ultrawideband (UWB) applications is presented. The proposed antenna is composed of a radiant patch with a C-shaped slot and a C-shaped stub on the back surface of the substrate. By using the C-shaped slot and the C-shaped stub, dual-band-notched characteristics can be generated. In this way, a more practical and effective approach to design an UWB antenna with sharp notched-band-edge selectivity is developed. The measurement results show dual notched bands of 4.96–5.42 GHz and 5.71–5.91 GHz, which can reject the interference between IEEE 802.11a bands (5.15–5.35 GHz and 5.725–5.825 GHz) and UWB systems. The fabricated antenna shows good omnidirectional radiation patterns with acceptable gain and group delay.